Labour and poverty in rural Tanzania: Ujamaa and rural development in the United Republic of Tanzania - Collier, P; Radwan, S; Wangwe, S (1986)
Assesses Tanzania's experience in rural development. Analysis is based on the results of the household and village survey conducted by the International Labour Office and the Department of Economics at Dar es Salaam University in 1980, covering a randomly chosen sample of 600 households in 20 villages in 8 regions. Begins with a review of rural development issues and policies and identifies and measures inequality, showing its extent both within and among villages. Describes the household and village surveys, presents a profile of the village household and the village community, and discusses peasant differentiation. Investigates the impact of government programs such as cooperative farms, land reform, education, and health services. Concludes that reform of the agrarian economy is the key to coping with the present development problems. Collier is a Fellow of Keble College, Oxford University; Radwan is Senior Economist with the International Labour Organization's World Employment Programme; and Wangwe is Dean of the Faculty of Arts at the University of Dar es Salaam, Tanzania. Index.